Situation actuelle et perspectives de développement du palmier dattier au Maroc - Haddouch M. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
This paper presents the date palm situation in Morocco. It draws back palm date history sector, describes its actual situation, defines the most relevant constraints and points out strategic orientations to develop palm date sector at national level.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)